Static stability study of stiffened functionally graded composite plates reinforced by carbon nanotubes using finite element method - Chung, Nguyen Thai; Thu, Duong Thi Ngoc (Vietnam Journal of Mechanics, 2023)
This paper presents some results on the linear stability research of Stiffened Functionally Graded Carbon NanoTube-Reinforced Composite (SFG-CNTRC) plates under static in-plane loads by the Finite Element Method (FEM) and a new four-variable refined plate theory. The governing equations for the static buckling of the system are obtained by the new four-variable refined plate theory and FEM. The eigenvalue problem method was used to solve the equation to determine the critical force of the plates. A numerical example is compared with the results in another research to check the validity of the present algorithm. The influences of some factors such as plate theory, CNT distribution along the layer thickness, stiffener height ratio, and fiber orientation angle on the critical buckling loads and unstable regions are discussed.